Colocalization Analysis of Cytoplasmic Actin Isoforms Distribution in Endothelial Cells - Anton S. Shakhov; Polina A. Kovaleva; Alexandra S. Churkina; Igor I. Kireev; Irina B. Alieva (Biomedicines, 2022)
Actin cytoskeleton is an essential component of living cells and plays a decisive role in many cellular processes. In mammals, β- and γ-actin are cytoplasmic actin isoforms in non-muscle cells. Despite minor differences in the amino acid sequence, β- and γ-actin localize in different cell structures and perform different functions. While cytoplasmic β-actin is involved in many intracellular processes including cell contraction, γ-actin is responsible for cell mobility and promotes tumor transformation. Numerous studies demonstrate that β- and γ-actin are spatially separated in the cytoplasm of fibroblasts and epithelial cells; this separation is functionally determined. The spatial location of β/γ-actin in endothelial cells is still a subject for discussion. Using super-resolution microscopy, we investigated the β/γ-actin colocalization in endotheliocytes and showed that the β/γ-actin colocalization degree varies widely between different parts of the marginal regions and near the cell nucleus. In the basal cytoplasm, β-actin predominates, while the ratio of isoforms evens out as it moves to the apical cytoplasm. Thus, our colocalization analysis suggests that β- and γ-actin are segregated in the endotheliocyte cytoplasm. The segregation is greatly enhanced during cell lamella activation in the nocodazole-induced endothelial barrier dysfunction, reflecting a different functional role of cytoplasmic actin isoforms in endothelial cells.